OPTIMASI DESAIN SHELL AND TUBE HEAT EXCHANGER TIPE SINGLE SEGMENTAL BAFFLE DENGAN VARIASI JUMLAH BAFFLE DAN POTONGAN BAFFLE MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMIC - Fajri, Ahmed; Saputra, Trisma Jaya; Dewi, Rany Puspita (Jurnal Rekayasa Mesin, 2025)
The heat exchanger is a device used to transfer heat between two process streams. In general, the flow that occurs in shell and tube heat exchangers is parallel flow or counter flow. To change the flow in the shell and tube heat exchanger into the cross flow, baffles can be added. The ideal cutting for baffle cutting is taken 20% to 35% of the inner diameter of the shell while the baffle distance is one-fifth of the inside diameter (ID) of the shell or 2 inches. Shell type "E" consists of 9 tubes with a 45° square pattern arrangement and single segmental baffle type with different orientations of baffle spacing and cuts 6, 8, 10 baffles and 25% and 30% of the shell inner diameter. CFD simulation results were obtained in the form of temperature distribution contours, pressure flow profile. The analysis shows that a properly selected baffle spacing and cut has the maximum potential to improve the heat exchanger performance up to 59.15%, as shown in the heat exchanger with 10/25% configuration. Increasing the number of baffles can increase the effectiveness-NTU by about 11% to 13%, while the same baffle spacing with different baffle cuts shows that 30% baffle cuts can reduce the pressure drop problem by about 8% to 11% compared to 25% baffle cuts.